Economic comparison of hungarian and polish egg-producing companies - Ricz, Sándor; Szőllősi, László (Studia Mundi – Economica, 2022)
The aim of the study is to evaluate the economic performance of Hungarian and Polish egg-producing companies, to explore differences, and to assess sectoral concentration. During the research work EMIS (Emerging Market Information System) database was used. Economic data of Hungarian (28) and Polish (34) companies engaged in table egg production was downloaded, filtered based on various parameters and processed for the business years 2017-2020. Descriptive statistical methods were used to process the data, inter-class frequency analysis was performed, and two-sample t-tests were used. Correlation analysis was performed to examine the correlations between the efficiency indicators (Return on Sales, Return on Equity, Return on Assets) and the data that expressing the plant size (sales revenue, balance sheet total). The results show that Polish companies have a larger plant size and are on average five times larger than Hungarian companies in sales revenue. However, there is no statistically significant difference in the profitability of production between the egg-producing companies in the two countries. However, there is a statistical relationship between profitability and farm size, which shows that the principle of economies of scale applies in this sector as well. Based on all this, further concentration and increase of farm size is proposed for the Hungarian domestic egg sector, which – among other factors – can also improve international competitiveness.